The Impact of Parental Financial Teaching on University Students’ Financial Attitudes: The Mediating Role of Self-Control - Andrey Hasiholan Pulungan; Dhiya Aufa Abdurrahman; Billian Canara; Rizki Ramadhan (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2024)
Most university students, who are in the process of transitioning from adolescence to adulthood, face difficulties managing their finances independently. To overcome these obstacles, students must have a positive financial attitude. This research aims to investigate both the direct and indirect impacts of parental financial teaching on students’ financial attitudes. In particular, the study examines the mediating effect of self-control on the relationship between financial education by parents and financial behaviors among accounting students. A survey was employed online to 219 accounting students in four different universities in October – December 2023. The data was then analyzed by applying SMART-PLS 4. The results of the analysis indicate that parental financial education tends to improve students’ behaviors in managing their finances. Furthermore, students who receive parental financial teaching are more likely to have positive self-control, which then positively affects their financial behaviors. This study enhances the existing finance literature and practice by demonstrating that improved parent-child communication can lead to the development of strong self-control in students when it comes to managing their finances. Keywords: Parental financial teaching, Financial attitude, Self-control, University students